The Role of Nutrition Education and Access to Digital Information for Working Parents in the Success of Providing Complementary Foods in Indonesia - Fitri, Salsabila Dwi; Ananta, Yorasaki (Dinasti Health and Pharmacy Science, 2024)
Giving Food Complementary breast milk (MPASI) is crucial in growth and development of a child. However, in working parents’ context, success?? Providing complementary food often faces problems various challenges, especially limitations time and access information. This article aiming For to study role education nutrition and access digital information on success giving complementary food to parents working in Indonesia. The method used is study library with approach Systematic Literature Review (SLR), with source article from Google Scholar, Mendeley, and journals academic relevant others. Study results show that education nutrition plays an important role in increasing parental knowledge and skills? in preparing appropriate MPASI standard. While accessing digital information becomes tool help strategic for parents? Work in to obtain information in a way flexible and efficient. This article formulates two main hypotheses for study next: (1) education nutrition plays a positive role to success provision of complementary foods, and (2) access to digital information also has a positive role to success of MPASI. Findings This emphasize importance integration between educational strategies and utilization technology information in intervention health child age early in Indonesia.